Advances in Neuropathologic Research of Hypoglycemic Brain Damage Caused by Insulin Overdose - TONG Fang, YANG Yi, LIANG Yue, et al. (Fayixue Zazhi, 2020)
The number of death from insulin overdose, including accidental poisoning, suicide and homicide, is increasing these years. The forensic diagnosis of death from insulin overdose is a tough task. Glucose is the main energy source of the brain. Therefore, hypoglycemic brain damage is considered to be the main reason of death from insulin overdose. Recently, research of hypoglycemic brain damage caused by insulin overdose is gradually being paid attention in the field of forensic medicine. This paper summarizes the neuropathologic changes, pathophysiologic process and potential neural molecular markers of hypoglycemic brain damage caused by insulin overdose in terms of forensic neuropathology, providing reference for the research and practice in forensic medicine related fields.